Washback effects of multiple-choice, cloze and metalinguistic tests on EFL students writing - Shirzadi, Danial; Amerian, Majid (Universitas Pendidikan Indonesia, 2020)
The washback effects of different test formats on the writing performance of students have always been of great importance. However, this area of research has not fully touched upon by researchers of second language testing. Despite the importance of the issue, there is a dearth of empirical studies to unravel the effects of different types of tests on learning. To shed some light on the current issue, the present study intends to look into the washback effects of tests on students who are learning and using some special grammatical points in writing tasks. In order to fulfil this project, we made a set question in three formats of cloze, multiple-choice and metalinguistic on a grammatical form(i.e. present perfect and present perfect continuous)to use after each session of teaching (2 sessions of training) as an activity. The researchers devised and validated three tests on the target form; each test contained 20 questions and was in different formats of cloze, multiple-choice or metalinguistic. At the end of this two-session trainings, two focused writing tasks were implemented. The results indicated that supporting teaching grammatical points with metalinguistic tests yields the highest positive washback on students writing. Finally, some practical implications were suggested.